Infusion Center Guidelines for Teprotumumab Infusions: Informed Consent, Safety, and Management of Side Effects. Issue 6 (November 2021) - Kang, Julia; Lechuga, Maria; Braun, Jenna; Kossler, Andrea; Douglas, Raymond; Cockerham, Kimberly
Abstract : Teprotumumab was the first and only medication approved by the US Food and Drug Administration for the treatment of thyroid eye disease in January 2020. Thyroid eye disease is a complex autoimmune inflammatory disease that can be sight-threatening, debilitating, and disfiguring to affected patients. Although biologic therapies are a preferred treatment option for many complex immunologic and oncologic conditions, their use in ophthalmology and endocrinology may be more novel. The goals of this article are to introduce this new therapeutic option; discuss its mechanism of action, indications for use, administration protocol, infusion precautions, and informed consent; and review common side effects and management.